2001
DOI: 10.14430/arctic770
|View full text |Cite
|
Sign up to set email alerts
|

Remote Identification of Polar Bear Maternal Den Habitat in Northern Alaska

Abstract: ABSTRACT. Polar bears (Ursus maritimus) give birth in dens of ice and snow to protect their altricial young. During the snowfree season, we visited 25 den sites located previously by radiotelemetry and characterized the den site physiognomy. Seven dens occurred in habitats with minimal relief. Eighteen dens (72%) were in coastal and river banks. These "banks" were identifiable on aerial photographs. We then searched high-resolution aerial photographs (n = 3000) for habitats similar to those of the 18 dens. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 15 publications
2
37
2
Order By: Relevance
“…Dens are known to be important, and carefully constructed or selected, resources for various carnivores: wolves "Canis lupus" [1,2], arctic foxes "Alopex lagopus" [3,4], gray foxes "Urocyon cinereoargenteus" [5], polar bears "Ursus maritimes" [6], lynx "Lynx Canadensis" [7], wolverines "Gulo gulo" [8], otters "Lutra Canadensis" [9], and skunks "Spilogale gracilis" [10] are all examples of Carnivora that have been found to utilize dens in locations that can be predicted from topography, pedology, and/or habitat characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Dens are known to be important, and carefully constructed or selected, resources for various carnivores: wolves "Canis lupus" [1,2], arctic foxes "Alopex lagopus" [3,4], gray foxes "Urocyon cinereoargenteus" [5], polar bears "Ursus maritimes" [6], lynx "Lynx Canadensis" [7], wolverines "Gulo gulo" [8], otters "Lutra Canadensis" [9], and skunks "Spilogale gracilis" [10] are all examples of Carnivora that have been found to utilize dens in locations that can be predicted from topography, pedology, and/or habitat characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…These centres divide the region into convex polygons or tiles, one per centre, each consisting of all points nearer to that centre than to any other. Doncaster and Woodroffe's (1993) model showed that the size and configuration of territories could be predicted quite accurately solely on the basis of sett location. This led them to hypothesise that setts were critically limiting resources and thus that setts determined the population's spatial organisation.…”
mentioning
confidence: 99%
“…Dens are known to be important resources amongst various carnivores, so the proposition that they are crucial to badger spatial organisation is certainly plausible. Wolves, Canis lupus (Ballard et al 1991, Norris et al 2002, arctic foxes, Alopex lagopus (Smith et al 1992, Nielsen andPedersen 1994), polar bears, Ursus maritimes (Durner et al 2001), lynx, Lynx canadensis (Slough 1999), wolverines, Gulo gulo (Magoun and Copeland 1998) and skunks, Spilogale gracilis (Crooks 1994) are all examples from the Carnivora of species that have been found to construct dens in locations that can be predicted from topography, pedology, aspect and/or habitat characteristics. Doncaster and Woodroffe (1993) used a Dirichlet tessellation (Stoyan et al 1987, Byers 1992 to simulate badger territories.…”
mentioning
confidence: 99%
“…Dashes indicate that the given variable was unavailable for the given model set. islands with only a few metres height provide drifts for dens in large flat areas with few good alternatives (Durner et al 2001;Durner et al 2003;Durner et al 2013).…”
Section: Survey Methodsmentioning
confidence: 99%